Growth Performance and Hematology of Khao Lamphun Calves with the Implementation of Creep Feeding - Suerphang, C.; Sittiboonma, A.; Sorachakura, C.; Intawicha, P.; Panase, P.; Laorodphan, N.; Dongpaleethun, C.; Chiang, H. I.; Ju, J. C. (Tropical Animal Science Journal, 2025)
The study aimed to evaluate the effect of creep feeding on growth performance and the hematological and biochemical profiles of Khao Lamphun calves. Twenty Khao Lamphun cow-calf pairs were randomly allotted into two treatments: T1, no supplementation of creeping feed (n=10), and T2, with concentrates as creep-feeding (n=10). Production or growth performance was evaluated based on body weight gain (BWG), heart girth (HG), hip height (HH), and body length (BL) throughout the experimentation. By day 120, the final live weight of the creep-fed calves was greater than the non-creep-fed calves, p